PdPANA: phagemid display as peptide array for neutralizing antibodies, an engineered in silico vaccine candidate against COVID-19 - Uzcátegui, Javier; Mullah, Khaleel; Buvat de Virgini, Daniel; Mendoza, Andrés; Urdaneta, Rafael; Naranjo, Alejandra (Frontiers in Systems Biology, 2024)
The COVID-19 pandemic has tested the technical, scientific, and industrial resources of all countries worldwide. Faced with the absence of pharmacological strategies against the disease, an effective plan for vaccinating against SARS-CoV-2 has been essential. Due to the lack of production means and necessary infrastructure, only a few nations could adequately confront this pathogen with a production, storage, and distribution scheme in place. This disease has become endemic in many countries, especially in those that are developing, thus necessitating solutions tailored to their reality. In this paper, we propose the design of a thermally stable, universal, efficient, and safe COVID-19 vaccine based on in silico design against SARS-CoV-2 through bioinformatics, immunoinformatics, and molecular modeling approaches for the selection of antigens with higher immunogenic potential, incorporating them into the surface of the M13 phage. Our work focused on using phagemid display as an array of peptides for identifying neutralizing antibodies (PdPANA). All of this was achieved using open-source software tools and servers, providing common resources for such health-focused research efforts. This alternative proposal not only demonstrates its ability to confer immunity and safety in potential administration but also suggests cost-effectiveness in production, durability, and ease of distribution under less stringent thermal conditions compared to existing methods. Our results indicate that the glycosylation region of the SARS-CoV-2 Spike protein (aa 344-583) proves to be an ideal protein target for the M13 phagemid display system. The paper also outlines the system's limitations and potential for each stage of development.